2008
DOI: 10.1002/app.29073
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradation of oxo‐biodegradable polyethylene

Abstract: Biodegradation of polyethylene and oxobiodegradable polyethylene films was studied in this work. Abiotic oxidation, which is the first stage of oxobiodegradation, was carried out for a period corresponding to 4 years of thermo-oxidation at composting temperatures. The oxidation was followed by biodegradation, which was achieved by inoculating the microorganism Pseudomonas aeruginosa on polyethylene film in mineral medium and monitoring its degradation. The changes in the molecular weight of polyethylene and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
46
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(61 citation statements)
references
References 26 publications
6
46
1
Order By: Relevance
“…Reddy et al [27] revealed that the β-carbons of hexadecane were oxidized repetitively into carboxylic acid groups and the alkane chain was cleaved by way of the formation of the acetyl-coenzyme A.…”
Section: These Include Penicillium Simplicissimum Brevibacillus Borsmentioning
confidence: 99%
“…Reddy et al [27] revealed that the β-carbons of hexadecane were oxidized repetitively into carboxylic acid groups and the alkane chain was cleaved by way of the formation of the acetyl-coenzyme A.…”
Section: These Include Penicillium Simplicissimum Brevibacillus Borsmentioning
confidence: 99%
“…This type of experiments allows a better understanding of the process fundamentals, while it could also become the basis of standardised, easy to reproduce tests. Biodegradation with defined microbial strains was evaluated in several studies, most recently with Pseudomonas aeruginosa strain [6,7]. The authors brought some rather qualitative evidences that bacteria used some substances from polyethylene to support their metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, the study on environmentally friendly plastics became the interest of many research groups. [16][17][18] From the literature, it is suggested that the oxo-materials could reduce the degradability time of the plastics to 2-5 years in the United Kingdom. In the first method, plastics are made from renewable feedstocks such as polyhydroxyalkanoates and polylactic acid (PLA).…”
Section: Introductionmentioning
confidence: 99%
“…Fe2 + + ROO: + H + In the third step, by the reaction of radicals, the carbonyl groups could be produced. 17 In both researches, burying the samples underground could have significant effects on their decomposition. 18 There are many studies in the oxo-material degradability properties.…”
Section: Introductionmentioning
confidence: 99%